ILCA glossary of livestock and related terms. English-French - International Livestock Centre for Africa (International Livestock Centre for Africa, 1996)
This handy glossary (giving French equivalents of alphabetically listed English terms but not vice versa), was compiled by staff at the ILCA French Copy Unit in Addis Ababa over a period of more than 10 years, and is sure to become a most useful aid for translators, interpreters and scientists working in the various fields of animal agriculture (including feed crop production). The pocket-sized volume contains around 3500 entries and 9000 sub-entries, comprising an extremely wide variety of traditional and modern terms, ranging from 'culvert', 'outreach' and 'artificial insemination gun' to 'flea', 'downloading', 'rotating savings' and 'credit association'. Frequent revisions of the glossary are promised and comments and suggestions for future editions are invited, although no mention is made of plans for a French-English edition.